Effective enhancement of electrochemical properties of LSM oxygen electrode in SOCs by LNO nano-catalyst infiltration - Zohreh Akbari; Alireza Babaei; Abolghasem Ataie (Journal of Ultrafine Grained and Nanostructured Materials, 2018)
In this paper, the effects of infiltration of La2NiO4 (LNO) as a mixed ionic and electronic conductor (MIEC) on the electrochemical performance of porous strontium doped lanthanum manganite (LSM) oxygen electrode of solid oxide cells, in the temperature ranges of 650-850 °C, is reported. XRD and FE-SEM results of the LNO sample calcined at 900 °C confirmed the formation of single phase LNO nanoparticles and uniform distribution of LNO into the porous LSM backbone with a mean particle size of 40 nm, respectively. To characterize the electrochemical behavior of half-cells, electrochemical impedance spectroscopy (EIS) measurement at temperature intervals of 50 °C was carried out. The LNO infiltrated LSM electrodes showed a noticeably decreased activation energy (from 130 to 103 kJ mol-1) and polarization resistance (from 26.2 to 2.5 Ωcm2 at 650 °C) under open circuit voltage (OCV) condition. Besides, the equivalent circuit (EC) modeling revealed that LNO addition has a major effect on the low frequency arc, which is attributed to the surface exchange mechanisms. Decreased amounts of activation energy and polarization resistance of the infiltrated LSM electrode compared to those for the pure one suggest that introduction of LNO nano-particles to the microstructure of LSM is a promising approach to achieve better electrochemical performance even in the low temperature of 650°C.